PENGARUH KOMUNIKASI INSTRUKSIONAL TERHADAP HASIL BELAJAR SISWA: STUDI PADA SISWA KELAS XI MATA PELAJARAN KEARSIPAN MANAJEMEN PERKANTORAN DAN LAYANAN BISNIS (MPLB) SMK BINA WISATA LEMBANG) - Fhebi Natasya Grace br Ginting, - (2023)
This research examines the problem of not maximizing the learning outcomes of Class XI MPLB students in the Archives Subject at the Bina Wisata Lembang Vocational School as seen from the final semester assessment for 2018/2020. This research consists of two variables, namely Instructional Communication (X) and Learning Outcomes (Y). This study aims to describe the effectiveness of Instructional Communication, describe the level of Student Learning Outcomes and determine the effect of Instructional Communication on Student Learning Outcomes in Archives Class XI Office Management and Business Services (MPLB) at SMK Bina Wisata Lembang. This research uses a Quantitative Approach with an explanatory survey method. The data collection technique was carried out by distributing questionnaires or questionnaires with a Likert scale model. The population in this study were students of class XI MPLB at SMK Bina Wisata Lembang with a total of 102 students. By using the Simple random sampling technique, a sample of 50 students was obtained. Data analysis technique using simple regression analysis. Based on the results of the study, the Instructional Communication variable is in the very high category and learning outcomes are in the high category. The results of the hypothesis test show that there is a positive and significant effect of Instructional Communication on student learning outcomes.